Groundwater exploration using resistivity and magnetic data at the northwestern part of the Gulf of Suez, Egypt - Abdel Galil A. Hewaidy; Essam A. El-Motaal; Sultan A. Sultan; Talaat M. Ramdan; Ahmed A. El khafif; Shokry A. Soliman (Egyptian Journal of Petroleum)
The present study aims to investigate the ground water accumulations present in the area located west of the Gulf of Suez, to face the new urbanization settlements of industrial national projects in the study area using geoelectrical and magnetic measurements. Magnetic data interpretation was carried out using the RTP magnetic data (or, through analyzing the RTP aeromagnetic map) to determine the depth to the surface of basement rocks and delineate the trends of structural elements. The results of magnetic interpretation indicated that the depth to the basement surface is ranging from 1200 to 3500 m and the trends of encountered structural elements are mainly NE–SW, NW–SE, NNW–SSE and E–W directions. Seventeen vertical electrical soundings of Schlumberger configuration were measured with AB/2 ranging from 1.5 m to 1500 m at the southern part of the study area. The results of quantitative interpretation of geoelectrical data indicated that the subsurface section consists of six different geoelectrical units; the first unit represents the Quaternary gravel and sand of high resistivity values and thickness of about a few meters. The second geoelectrical unit exhibits moderate resistivity values ranging from 23 to 100 ohm m and thickness ranging from 4.5 to 67 m which represents the fresh water aquifer in the study area, while the lithology of this layer consists of sandstone and limestone which belongs to the Upper Miocene. The third geoelectrical unit is composed of sandy clay and limestone which belongs to the Middle Miocene deposits and shows low resistivity values ranging from 6 to 7 ohm m and thickness ranging from 44.5 m to 66 m. This third layer represents the second aquifer (brackish water). The fourth geoelectrical unit consists of limestone and clayey limestone which belongs to the Lower Miocene deposits and exhibits moderate resistivity values ranging from 16 to 33 ohm m, while the thickness of this unit ranges from 47–102 m. This layer represents the third aquifer (brackish water). The fifth geoelectrical unit reveals very low resistivity values of about 2–5 ohm m and consists of clay and sandstone of the Oligocene and Upper Eocene deposits. The sixth geoelectrical unit is the bottommost unit in the studied subsurface section and exhibits moderate resistivity values in a range of about 22–35 ohm m and consists of limestone of the Middle Eocene deposits.